(3/(2m+4))=(1/(m+2))-2

Simple and best practice solution for (3/(2m+4))=(1/(m+2))-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3/(2m+4))=(1/(m+2))-2 equation:


D( m )

2*m+4 = 0

m+2 = 0

2*m+4 = 0

2*m+4 = 0

2*m+4 = 0 // - 4

2*m = -4 // : 2

m = -4/2

m = -2

m+2 = 0

m+2 = 0

m+2 = 0 // - 2

m = -2

m in (-oo:-2) U (-2:+oo)

3/(2*m+4) = 1/(m+2)-2 // - 1/(m+2)-2

3/(2*m+4)-(1/(m+2))+2 = 0

3/(2*m+4)-(m+2)^-1+2 = 0

3/(2*m+4)-1/(m+2)+2 = 0

(3*(m+2))/((2*m+4)*(m+2))+(-1*(2*m+4))/((2*m+4)*(m+2))+(2*(2*m+4)*(m+2))/((2*m+4)*(m+2)) = 0

3*(m+2)-1*(2*m+4)+2*(2*m+4)*(m+2) = 0

4*m^2+m+16*m+2+16 = 0

4*m^2+17*m+18 = 0

4*m^2+17*m+18 = 0

4*m^2+17*m+18 = 0

DELTA = 17^2-(4*4*18)

DELTA = 1

DELTA > 0

m = (1^(1/2)-17)/(2*4) or m = (-1^(1/2)-17)/(2*4)

m = -2 or m = -9/4

(m+9/4)*(m+2) = 0

((m+9/4)*(m+2))/((2*m+4)*(m+2)) = 0

((m+9/4)*(m+2))/((2*m+4)*(m+2)) = 0 // * (2*m+4)*(m+2)

(m+9/4)*(m+2) = 0

( m+2 )

m+2 = 0 // - 2

m = -2

( m+9/4 )

m+9/4 = 0 // - 9/4

m = -9/4

m in { -2}

m = -9/4

See similar equations:

| 3/2Y-1/2=-3/5Y-5 | | 10e-2-9=39 | | 8b+12-b=+8+7b+4 | | Y=2500(.85)x | | (3x+20)+(5x-50)=180 | | -2(x-1)-3=8-4x | | 12x+4y+8=0 | | x+4-3x=2x-3-1 | | 3x+54/7+x+17/5=13 | | -2x=-2+14 | | 2(3x+1)+3(x+4)= | | 6+p/2=-7 | | N+(n+2)+(n+4)+(n+6)=8 | | Y=1200(.85)x | | -1/3W-5=4/5W+4/5 | | 0.2t=0.6+0.7t | | 4m^2=(n+4)(2-m) | | 14x-79=8-25 | | S+7/2s+10=46 | | 13=5/13(4-2x)^2 | | -7X+1/4=-1/3X-7/4 | | 3x+4-2x+5=6x+2 | | 2ax-5ac=3c(a+4) | | Y=2500*.88x | | 15=3x+3(2x-4) | | 4m^2=(n+4)(2-n) | | 3z-17+2z=14 | | -4x-3(6x-5)=169 | | F(x)=7.50x-20000 | | 9-1m=20 | | 7n-5(1-7n)=331 | | -22m=42 |

Equations solver categories